Employing Qualitative Methods in Developing Functional Requirements for Electronic Records Management Research - Hussin, Nurussobah; Akmar Ismail, Saidatul; Farik Mat Yatin, Saiful; Nazir Ahmad, Mohd; Shamsul Mohd Shoid, Mohd (International Journal of Engineering and Technology, 2018)
This paper explores the justification of using a qualitative research method under the participatory paradigm. In order to develop the functional requirements of electronic court records management system in Malaysian Judiciary, the case study approach was chosen. The discussion begins by presenting the descriptions of methodology and methods employed, followed by the authorsâ€™ philosophical stance and the rationale for choosing a qualitative approach. Besides analysing the philosophical stance, the analysis of methods used in previous studies also provided insightful findings that helped ascertained the appropriate research method of the study. The development of twelve stages in developing the functional requirements specification based on the analysis of seven previous studies could be a reference material for other researchers. It is hoped that the knowledge that emerged when the functional requirements were developed could benefit readers and enhance their ability to apply as closely as possible to other studies or to make modifications for further research.Â Â